P711 The real-life experience of vedolizumab therapy in the OBSERV-IBD cohort: a 3-year prospective observational multi-centre cohort study. (25th January 2019) - Amiot, A; Serrero, M; Peyrin-Biroulet, L; Filippi, J; Pariente, B; Roblin, X; Buisson, A; Stefanescu, C; Trang-Poisson, C; Altwegg, R; Marteau, P; Vaysse, T; et al.
Abstract: Background: Population-based studies have confirmed effectiveness and safety of vedolizumab in treating patients with UC and CD, but data beyond 1 year are laking. Herein, we provide effectiveness and safety data of vedolizumab therapy in the OBSERV-IBD cohort with a 3-year follow-up period. Methods: Between June and December 2014, 173 patients (64 males; median age 34.7 [IQR: 27.9–45.4] years) with CD and 121 with UC (67 males; median age 40.1 [29.8–54.4] years) were treated with vedolizumab therapy. Among them, 149 were still treated with vedolizumab beyond Week 54 (78 patients with CD and 71 with UC). Disease activity was assessed using the Harvey–Bradshaw Index for CD and the partial Mayo Clinic score for UC. Clinical remission was defined as HBI ≤4 for CD patients and a partial Mayo Clinic score < 3 with a combined stool frequency and rectal bleeding subscore of ≤1. The steroid-free clinical remission rates were computed at Weeks 81, 108, 135 and 162 to the whole population included at week 0. The probability of persistence of vedolizumab therapy was studied with Kaplan–Meier method, log-rank test and Cox regression model. Results: A total of 92 patients completed the 162-week maintenance period, including 43 in the CD group and 49 in the UC group. In the CD group, steroid-free clinical remission rates at Weeks 81, 108, 135 and 162 were 30%, 24%, 24% and 20%, respectively. In the UC group, steroid-free clinical remission rates at Weeks 81, 108, 135 and 162 were 40%, 33%, 34% and 36%, respectively. Vedolizumab dose optimisation occurred up to 59% and 52% up to week 162 in patients with CD and UC, respectively. The 1-, 2- and 3-year persistence rates of vedolizumab were 48.5%, 31.4% and 26.3% in patients with CD and 61.0%, 49.9% and 42.9% for UC, respectively. In the CD group multi-variate analysis, the persistence of vedolizumab was significantly decreased in patients with history of perianal disease (OR = 0.62, 95% CI[0.43–0.90], p = 0.01) and increased in patients with an age at induction of vedolizumab therapy > 35 years (OR = 1.47, 95% CI[1.01–2.13], p = 0.005). In the UC group multi-variate analysis, the persistence of vedolizumab was significantly decreased in patients with partial Mayo Clinic score > 6 at week 0 (OR = 0.43, 95% CI[0.25–0.74], p = 0.003) and in patients with UCEIS > 5 at week 0 (OR = 0.55, 95% CI[0.32–0.94], p = 0.03). No new safety signal was identified. Conclusions: In the OBSERV-IBD cohort study, vedolizumab was able to maintain steroid-free clinical remission in approximately one third of patients with UC and CD up to Week 162. Loss of response resulting in discontinuation of vedolizumab occurred in approximately 10% of the patients per year.